Permanent Residency and Refugee Immigrant Skill Investment - Jacob Arendt; Christian Dustmann; Hyejin Ku (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2023)
We analyze an immigration reform in Denmark that tightened refugee immigrants' eligibility criteria for permanent residency to incentivize their labor market attachment and acquisition of local language skills. Contrary to what the reform intended, the overall employment of those affected decreased while their average language proficiency remained largely unchanged. This was caused by a disincentive effect, where individuals with low prereform labor market performance reduced their labor supply. Our findings suggest that stricter permanent residency rules, rather than incentivizing refugees' skill investment, may decrease the efforts of those who believe they cannot meet the new requirements.
Keywords: J22; J24; J61; 330; immigrant assimilation; refugee integration; labor supply; language proficiency; human capital